The Cardassian expansion revisited: constraints from updated Hubble parameter measurements and type Ia supernova data. Issue 1 (1st February 2018) - Magaña, Juan; Amante, Mario H; Garcia-Aspeitia, Miguel A; Motta, V
Abstract: Motivated by an updated compilation of observational Hubble data (OHD) that consist of 51 points in the redshift range of 0.07 <  z  < 2.36, we study an interesting model known as Cardassian that drives the late cosmic acceleration without a dark energy component. Our compilation contains 31 data points measured with the differential age method by Jimenez & Loeb (2002 ), and 20 data points obtained from clustering of galaxies. We focus on two modified Friedmann equations: the original Cardassian (OC) expansion and the modified polytropic Cardassian (MPC). The dimensionless Hubble, E ( z ), and the deceleration parameter, q ( z ), are revisited in order to constrain the OC and MPC free parameters, first with the OHD and then contrasted with recent observations of type Ia supernova (SN Ia) using the compressed and full joint-light-analysis (JLA) samples (Betoule et al.). We also perform a joint analysis using the combination OHD plus compressed JLA. Our results show that the OC and MPC models are in agreement with the standard cosmology and naturally introduce a cosmological-constant-like extra term in the canonical Friedmann equation with the capability of accelerating the Universe without dark energy.